Infinite-shear viscosity plateau of salt-free aqueous xanthan solutions - Dakhil, Haider; Auhl, D.; Wierschem, Andreas (Journal of Rheology, 2019)
We study aqueous xanthan solutions at shear rates up to about 105 s-1. At these shear rates, the salt-free solutions show an infinite-shear viscosity plateau. Depending on the xanthan concentration, we find two different regimes with scaling laws well known for the zero-shear viscosity of dilute and semidilute solutions: The crossover concentration is considerably higher than in the first Newtonian branch, which can be related to the orientation of the polyelectrolytes. In the second regime, the normal stress differences increase with an exponent of about 1, indicating that the polymer solution behaves like nematic liquid crystals or rigid fiber suspensions. In the first regime, the exponent is smaller suggesting that the polyelectrolytes behave more flexible.
CRIS-Team Scopus Importer:2019-08-09